Poetry in Motion: 100 Years of Zanzibar's Nadi Ikhwan Safaa. Directed by Ron Mulvihill. Produced by Kelly Askew and Werner Graebner. DVD. 2016. Distributed by Jahazi Media Gris-Gris Films. Subtitles in Arabic, English, French, Swahili. 71 minutes. Available at www.poetryinmotionfilm.com. - Gunderson, Frank (International Library of African Music, 2016)
pages: 227-228
Keywords: African Music